2019
DOI: 10.1186/s40352-019-0097-6
|View full text |Cite
|
Sign up to set email alerts
|

Hearing and justice: The link between hearing impairment in early childhood and youth offending in Aboriginal children living in remote communities of the Northern Territory, Australia

Abstract: BackgroundHigh prevalence of chronic middle ear disease has persisted in Australian Aboriginal children, and the related hearing impairment (HI) has been implicated in a range of social outcomes. This study investigated the association between HI in early childhood and youth offending.MethodThis was a retrospective cohort study of 1533 Aboriginal children (born between 1996 and 2001) living in remote Northern Territory communities. The study used linked individual-level information from health, education, chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…The third implication is the importance of interagency collaboration, corroborating the recommendations of the Royal Commission which also stressed the need to develop a workforce equipped to deal with the complex needs of children who crossover between the child protection and youth justice systems [14]. This is particularly important in settings with relatively high prevalence of both child maltreatment reports and youth offending behaviour, such as the NT where it has also been established that community-level in uences contribute to the high risk of youth offending [64]. This and other similar studies also reinforce a separate recommendation of the Royal Commission calling for more research into place-based strategies for community safety and crime prevention [63] to inform a whole-of-community approach and inter-agency collaboration to child protection and youth justice.…”
Section: Persistence and Timing Of Cps Contactmentioning
confidence: 78%
“…The third implication is the importance of interagency collaboration, corroborating the recommendations of the Royal Commission which also stressed the need to develop a workforce equipped to deal with the complex needs of children who crossover between the child protection and youth justice systems [14]. This is particularly important in settings with relatively high prevalence of both child maltreatment reports and youth offending behaviour, such as the NT where it has also been established that community-level in uences contribute to the high risk of youth offending [64]. This and other similar studies also reinforce a separate recommendation of the Royal Commission calling for more research into place-based strategies for community safety and crime prevention [63] to inform a whole-of-community approach and inter-agency collaboration to child protection and youth justice.…”
Section: Persistence and Timing Of Cps Contactmentioning
confidence: 78%
“…Studies of community samples have similarly found a higher prevalence of maltreatment among females who offended relative to males who offended, including those examining likelihood of general offending, as well as specific offence types (Duke et al, 2010;He et al, 2019;Herrera & McCloskey, 2001). Studies examining gender differences in maltreatment among crossover samples involved in both the youth justice and child protection systems have produced more mixed findings (Baidawi & Sheehan, 2020a; Dirig,…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Hard of hearing students often regularly experience negative interactions with others. There is increasing evidence of adverse social and emotional outcomes associated with a history of ear disease (Hogan et al 2012;Zubrick et al 2006) and hearing loss (He et al 2019). Hearing loss has long-term negative social impacts, including limited employment options, increased risk of anti-social behavior (Howard 2005;Lowell 1994;Nienhuys and Burnip 1988) and involvement with the criminal justice system (Preston 1994;Vanderpoll and Howard 2012).…”
Section: Psychosocial Effects Of Hearing Lossmentioning
confidence: 99%
“…More than half of children who had child protection reports made about them in remote Northern Territory communities were found to have a history of hearing loss. Hearing loss and having child protection reports made were both associated with youth offending (He et al 2019). Currently, neither pre-service or in-service training of child protection workers in Australia includes any information on hearing loss impacting negatively on family communication and how to help mitigate these effects in at home or out of home care.…”
Section: Psychosocial Effects Of Hearing Lossmentioning
confidence: 99%